Analysis of the Rhythmic Accents of the Drum Instrument in the Song 'Mendung Tanpo Udan' Composed by Kukuh Prasetya - Laksono, Yonathan; Rachman, Abdul (Jurnal Penelitian Musik, 2025)
This study aims to Analysis of the Rhythmic Accents of the Drum Instrument in the Song 'Mendung Tapi Udan' by Kukuh Prasetya, as a key element in shaping the musical character of the dangdut ambyar genre. Background/Purpose of this research lies in the lack of in-depth studies on rhythmic fill-ins in drums, which significantly influence the musical atmosphere and identity of this genre.This research/Method employs a descriptive qualitative approach, with data collection techniques including observation, semi-structured interviews, and documentation. The data were analyzed through rhythmic transcription of the patterns found in the song.The results identify four rhythmic fill-in patterns, namely Pattern A, B, C, and D. These patterns combine quarter and eighth notes, emphasizing downbeats and upbeats that recur in specific sections of the song. These patterns contribute to building the energy, dynamics, and musical structure of the composition.Conclusions the drum fill-in technique not only reinforces the rhythmic elements but also serves as a distinctive marker of dangdut ambyar, differentiating it from other dangdut subgenres. These findings are expected to enrich the study of Indonesian popular music and support the continuity of dangdut as a traditional music genre that adapts to modern developments.